Upaya Non Penal Penanggulangan Pembakaran Hutan dan Lahan di Provinsi Lampung - Edla, Zalza Junior; Shafira, Maya; Farid, Muhammad; Maulani, Diah Gustiniati; Ginting, Mamanda Syahputra; Meidiantama, Refi (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2025)
Purpose: To purpose the non penal efforts in dealing with forest and land burning in Lampung Province. Methodology/approach: The methods used in this research are normative legal and empirical legal approaches, namely by conducting literature studies and field studies by seeking information through interviews. Result/findings: The findings show that based on data from the Lampung Regional Police (Polda), there have been no reports of forest and land fires in Lampung Province in recent years. However, data from the Ministry of Environment and Forestry shows that forest and land fires still often occur in the region. Therefore, overcoming criminal acts of forest and land burning requires serious and integrated efforts from various authorized parties. Conclusions: karhutla control in Lampung Province through non-penal efforts focuses on preventive and educational steps, such as counseling, patrols, and monitoring of hotspots by the Lampung Police and the Forestry Service. Collaboration with local governments, NGOs, and the community is the main strategy in reducing the number of karhutla. Meanwhile, non-penal efforts face obstacles such as limited personnel, minimal facilities, low public awareness, and the habit of clearing land by burning. Therefore, synergy between various parties is needed to increase the effectiveness of forest and land fire prevention and control. Limitations: This research only analyzes non-penal efforts to prevent forest and land fires in Lampung based on data from relevant agencies, without discussing the effectiveness of criminal law enforcement or the long-term impact of policies, apart from that, differences in reports from various sources are a challenge in obtaining a completely accurate picture of forest and land fire incidents in Lampung. Contribution: Making a positive contribution to agencies involved in preventing forest and land fires, so that they can play a more active role in improving law enforcement and protecting the community in the future.